2017
DOI: 10.1093/molehr/gax017
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, maintenance and functional integrity of the blood–testis barrier in organotypic cultures of fresh and frozen/thawed prepubertal mouse testes

Abstract: This work was supported by Rouen University Hospital, Ligue contre le Cancer (to L.D.), and co-supported by European Union and Région Normandie (to A.O.). Europe gets involved in Normandie with European Régional Development Fund (ERDF). The authors declare that they have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 61 publications
6
12
0
Order By: Relevance
“…In tubules containing spermatocytes or round spermatids a heterogeneous staining pattern with immunopositive and negative reactions was observable in the basal part of the seminiferous epithelium, apparently independent from the containing GC population. Such a heterogeneous immunostaining pattern for claudin-3 was also reported by Rondanino et al [ 83 ] in fresh testicular tissues. A possible explanation for the seemingly heterogeneous immunostaining results in the present study could be that different GC (sub)populations were not definitely determined in the histological sections at hand.…”
Section: Discussionsupporting
confidence: 83%
“…In tubules containing spermatocytes or round spermatids a heterogeneous staining pattern with immunopositive and negative reactions was observable in the basal part of the seminiferous epithelium, apparently independent from the containing GC population. Such a heterogeneous immunostaining pattern for claudin-3 was also reported by Rondanino et al [ 83 ] in fresh testicular tissues. A possible explanation for the seemingly heterogeneous immunostaining results in the present study could be that different GC (sub)populations were not definitely determined in the histological sections at hand.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, a study recently demonstrates that testicular function in cultured testis fragment model, as expressed in gene expression profiling and testosterone levels, is qualitatively similar to results observed in vivo 13 . However, the yield of spermatozoa produced in organotypic cultures is low compared with age‐matched in vivo control 14‐16 and our recent data showed that meiotic and post‐meiotic progression could be impaired in cultured testicular explants 16,17 …”
Section: Introductionsupporting
confidence: 70%
“…Due to the unique architecture and constant turnover of stem cells, prepubertal testes may be more prone to impairments in functionality due to the way they are handled, transported, and maintained. Although attempts to achieve in vitro spermatogenesis using mouse and human ITT have been reported [7,17,18,[28][29][30][31][32][33], to our knowledge, this is the first report comparing the functionality of ITT handled at different temperature and time periods before the organ culture is initiated. We believe that this is an important prerequisite for the successful in vitro generation of spermatozoa.…”
Section: Discussionmentioning
confidence: 97%